About the influence of antropogenic factors of pollution on increase of trophic level of lake Ak-Gel. - G. M. Abdurahmanov; G. A. Ahmedova; M. M. Rasulova (Юг России: экология, развитие)
During man's impact the process of eutrophication take peculiar features. The important role thereupon plays the waste water.